2018
DOI: 10.3390/geosciences8020050
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Flood Hazard at River Basin Scale with an Index-Based Approach: The Case of Mouriki, Greece

Abstract: Defining flood-prone areas is particularly important for policy makers, in order to design mitigation strategies and implement flood risk management planning. The present research applies a multicriteria index method to assess flood hazard areas at a river basin scale, in a geographic information system (GIS) environment. The developed methodology has been applied for an area in northeastern Greece, by processing information of seven parameters: flow accumulation, distance from the drainage network, elevation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The slope is strongly correlated to both the volume and the velocity of the surface runoff, as well as the infiltration to the groundwater. Flat areas flood quicker than inclined areas where runoff flows further down [22]. Refers to the slope class at the study location, we found that the slope is dominated by steep slope class (45-65%) (fig.…”
Section: B) Hazard Indexmentioning
confidence: 64%
“…The slope is strongly correlated to both the volume and the velocity of the surface runoff, as well as the infiltration to the groundwater. Flat areas flood quicker than inclined areas where runoff flows further down [22]. Refers to the slope class at the study location, we found that the slope is dominated by steep slope class (45-65%) (fig.…”
Section: B) Hazard Indexmentioning
confidence: 64%
“…A number of studies have used the multicriteria analysis method [21][22][23][24][25][26][27][28][29][30]. Hydraulic modeling using the HEC-RAS program is one of the most important methods used to model flood hazards in urban areas because it provides one-and two-dimensional models for the spread, depth, and speed of floodwater [6,9,[31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Floods can potentially cause fatalities, displacement of people and damage to the environment, to severely compromise economic development and to undermine the economic activities of every community that suffers the effects of these destructive environmental hazards (Patrikaki et al 2018;Zhong et al 2018;Birkholz et al 2014;Mouratidis and Sarti 2013;Yésou et al 2013;Astaras et al 2011). During the last decade, such phenomena have also plagued Greece, with their majority occurring in the eastern part of the region of Thrace (Kazakis et al 2015;Nikolaidou et al 2015;Mouratidis 2011;Mouratidis et al 2011).…”
Section: Introductionmentioning
confidence: 99%